A rare case of upper gastrointestinal hemorrhage due to tuberculous lymphadenitis fistulized in the duodenum - Souhaib Atri; Mahdi Hammami; Anis Belhadj; Faouzi Chebbi; Youssef Chaker; Montassar Kacem (International Journal of Emergency Medicine)
Abstract Introduction Abdominal tuberculosis is less prevalent than pulmonary tuberculosis. Tuberculous lymphadenitis accounts for fewer than 5% of abdominal cases. An unusual complication is the fistulization of a tuberculous lymph node into the digestive tract, with an even rarer association with upper gastrointestinal bleeding. Case Report A 63-year-old male with a history of rectal adenocarcinoma surgery presented with severe gastrointestinal bleeding that required multiple transfusions. Endoscopic attempts failed to locate the bleeding source, but CT angiogram revealed a hemorrhagic necrotic mesenteric lymph node with a fistula to the second part of the duodenum. The patient underwent surgery, which involved resecting the lymph nodes and disconnecting the fistula. Histopathological findings confirmed tuberculous mesenteric lymphadenitis, and the patient was subsequently started on HRZE therapy. Six months postoperatively, there was no recurrence of bleeding. Discussion Gastroduodenal tuberculosis is infrequent due to factors such as the high acidity of the gastric environment and limited lymphoid tissue. Symptoms may mimic other abdominal conditions, making diagnosis challenging. Common complications include gastric outlet obstruction and perforation, while gastrointestinal bleeding is rare. This case of hemorrhagic tuberculous lymphadenitis with fistulization highlights the need for a high index of suspicion and the role of imaging in diagnosing uncommon bleeding sources. While anti-tuberculosis therapy remains the primary treatment, surgery is warranted in cases involving refractory bleeding or fistulization. Conclusion This case emphasizes the importance of a multidisciplinary approach to abdominal tuberculosis with atypical presentations. Awareness of rare complications is essential for prompt diagnosis and management.